Enhancement of the Gain and the Bandwidth of a UWB Microstrip Patch Antenna Using Metamaterials - Faraj Darweesh, Ali; Ögücü Yetkin, Gölge (International Journal of Engineering and Technology, 2018)
This paper designs a miniaturized size ultra-wideband microstrip antenna based on Metamaterial array. The proposed structure is consisting of ultra-wideband antenna and Metamaterial array. The antenna is characterized by dimensions of 36*38*1.58 mm3 with a partial ground printed on the FR4 dielectric substrate. The MTM array is constructed from two triple split ring resonators located above the antenna structure. The antenna is showed an acceptable gain of 5.6 dB with a wide band of operating frequencies starting from 2.6 GHz to more than 20 GHz with an S11 value less than â€“ 10 dB in the entire band. The gain is enhanced about 3.19 dB by adding the TSRRs. Finally, the CST MWS is used to design and simulate the antenna structure.Â